Personal resilience resources predict post-stem cell transplant cancer survivors' psychological outcomes through reductions in depressive symptoms and meaning-making. Issue 6 (2nd November 2017) - Campo, Rebecca A.; Wu, Lisa M.; Austin, Jane; Valdimarsdottir, Heiddis; Rini, Christine
ABSTRACT: This longitudinal study examined whether post-transplant cancer survivors ( N = 254, 9 months to 3 years after stem cell transplant treatment) with greater personal resilience resources demonstrated better psychological outcomes and whether this could be attributed to reductions in depressive symptoms and/or four meaning-making processes (searching for and finding reasons for one's illness; searching for and finding benefit from illness). Hierarchical linear regression analyses examined associations of survivors' baseline personal resilience resources (composite variable of self-esteem, mastery, and optimism), which occurred an average of 1.7 years after transplant, and 4-month changes in psychological outcomes highly relevant to recovering from this difficult and potentially traumatic treatment: post-traumatic stress disorder (PTSD) symptoms and purpose in life. Boot-strapped analyses tested mediation. Greater personal resilience resources predicted decreases in PTSD stress symptoms ( b = −0.07, p = 0.005), mediated by reductions in depressive symptoms ( b = −0.01, 95% CI: −0.027, −0.003) and in searching for a reason for one's illness ( b = −0.01, 95% CI: −0.034, −0.0003). In addition, greater resilience resources predicted increases in purpose in life ( b = 0.10, p < 0.001), mediated by reductions in depressive symptoms ( b = 0.02, 95% CI: 0.003, 0.033). Having greater personal resilience resources may promote better psychological adjustment after a difficult cancer treatment, largely because of improvements in depressive symptoms, although decreased use of a potentially maladaptive form of meaning-making (searching for a reason for one's illness) was also important for reducing PTSD symptoms.